REGENERATIVE TREATMENT USING PERIODONTAL FLAP SURGERY COMBINED Ti-OSS®, PERICARDIUM MEMBRANE AND PLATELET-RICH FIBRIN IN CHRONIC PERIODONTITIS - Abyan Teguh Saputro; Vincensia Maria Karina (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Periodontal regenerative treatment with periodontal flap surgery followed by application of bone graft combined with platelet-rich fibrin (PRF) is a treatment using the concept of guided bone regeneration which is required to stimulate bone and periodontal tissue regeneration in chronic periodontitis with radiographic sign of alveolar bone vertical defect. This case report will describe the flap surgery with bone graft (Ti-OSS®, South Korea) and PRF treatment for correction of alveolar bone vertical defect in tooth with chronic periodontitis. Case: A 45-years old female complained of swollen and suppurated gingiva in the upper right area. Clinical finding showed deep periodontal pockets in tooth 13 and 15 and radiographic finding showed apical third alveolar bone loss in tooth 13 and 15. Case Treatment: Initial treatments included scaling and root planing, occlusal adjustment, and antibiotic prescription. Treatments were followed by periodontal flap surgery for debridement and elimination of granulation tissue on the root and alveolar bone surface of tooth 13 to 15, application of Ti-OSS® combined with PRF and pericardium membrane. Discussion: The follow-up evaluation 2 months after treatment showed clinical finding of decreased Clincial Attachment Level (CAL) and radiographic finding showed increased alveolar bone height around defect area of tooth 13 and 15. Conclusion and Suggestions: Periodontal flap surgery combined with application of Ti-OSS® and PRF may able to stimulate regeneration of alveolar bone and periodontal tissue in chronic periodontitis